Social media in attracting students in higher education: the missing incentive - Ribeiro, Thiago de Luca Sant’ana; Gonçalves, Gustavo Silva; de Lima, Anderson Antônio; de Oliveira, Marcos Antonio Maia Lavio (Retail Management Review, 2024)
Objective: The objective of this technical report is to present the processes and results of social media strategies in attracting students from two Brazilian higher education institutions (HEIs). Methodology: We chose the case study for this research because it represents, in general, the preferred strategy when asking questions such as ‘how’ and ‘why’. The central aspect of the case study is to increase in-depth understanding of the knowledge studied, as well as bringing greater reliability and trustworthiness to the cases. In this report, two real cases of recruiting IES students are presented with the results. Originality: In the educational sector, especially in higher education, social media has been used as an important tool for attracting students to higher education institutions (HEIs). Despite this, few studies work with real data in this segment. In this sense, it is important to understand the activities and real results of attracting students. Main results: Firstly, a table is presented summarizing the main social media activities implemented by HEIs A and B. Secondly, numbers of enrollees are presented by source of origin and by interaction with organic social media. Managerial Contributions: The set of results demonstrates that social media has two relevant roles in the processes of attracting students. Firstly, some leads originate through social media. In other words, potential enrollees get to know the HEI or the HEI content through social media (Instagram, Facebook, among others). Secondly, social media plays a role in nurturing leads, regardless of their source of origin.